Simulation-based evaluation of school reopening strategies during COVID-19: a case study of São Paulo, Brazil - Cruz, E. H. M.; Maciel, J. M.; Clozato, C.; Serpa, M. S.; Navaux, P. O. A.; Meneses-Rojas, Esteban; Abdalah, M.; Diener, M. (Instituto Tecnológico de Costa Rica, 2021)
During the COVID-19 pandemic, many countries opted for strict public health measures, including closing schools. After some time, they have started relaxing some of those restrictions. To avoid overwhelming health systems, predictions for the number of new COVID-19 cases need to be considered when choosing a school reopening strategy. Using a computer simulation based on a stochastic compartmental model that includes a heterogeneous and dynamic network, we analyze different strategies to reopen schools in the São Paulo Metropolitan Area, including one similar to the official reopening plan. Our model allows us to describe different types of relations between people, each type with a different infectiousness. Based on our simulations and model assumptions, our results indicate that reopening schools with all students at once has a big impact on the number of new COVID-19 cases, which could cause a collapse of the health system. On the other hand, our results also show that a controlled school reopening could possibly avoid the collapse of the health system, depending on how people follow sanitary measures. We estimate that postponing the schools’ return date for after a vaccine becomes available may save tens of thousands of lives just in the São Paulo Metropolitan Area compared to a controlled reopening considering a worst case scenario. We also discuss our model constraints and the uncertainty of its parameters.
Artículo. Campus Paranavaí, Federal Institute of Parana (IFPR), Paranavaí, Brazil, Informatics Institute, Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, Brazil, Costa Rica National High Technology Center, Costa Rica, Costa Rica Institute of Technology, Costa Rica, University of Illinois Urbana-Champaign, USA, 2021
Keywords: Estrategia de reapertura; COVID-19; Estudio de casos; Salud pública; Escuelas; Simulación por computadoras; Reopening strategy; Case study; Public health; Schools; Computer simulation; Research Subject Categories::TECHNOLOGY::Information technology::Computer science